Local smart specialisation: An approach to increasing preparedness in rural communities with resource-based industries in the Northern Periphery - Leneisja Jungsberg; Lise Byskov Herslund; Kjell Nilsson; Karina Umander; Anna Kantola; Jukka Teräs; Ryan Weber (Politecnico di Torino, 2020)
A common challenge for Northern communities is how to retain local benefit from resource-based industries. This study assesses the process of developing a local smart specialisation strategy in two municipalities, Storuman and Sodankylä, both located in the Northern Periphery. The assessment framework applied is based on the concept of ‘strategic dimensions’ (Healey, 2009), along with a qualitative set of process and outcome criteria (Innes and Booher, 1999). Our assessment of the strategic process indicates that all dimensions required for strategic planning were represented within it, but that they were mostly responsive rather than transformative in character. When comparing results from process criteria and outcome criteria, the process criteria score significantly higher. The strategic process engaged social networks and involved local stakeholders in discussion and joint prioritisation. According to the participating stakeholders, the local smart specialisation strategies in Storuman and Sodankylä enhanced local preparedness. However, a significant limitation was a lack of long-term human and financial resources to address challenges in relation both to resource-based industries and local territorial development.